2012
DOI: 10.15353/joci.v8i1.3070
|View full text |Cite
|
Sign up to set email alerts
|

Seniors Skyping: A Professional, Academic, and Community Collaboration

Abstract: The brief research report discusses a SKYPE project involving seniors in America and China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…At a broader level, our results are in accordance with the recent literature of technological acceptance (e.g. Caro et al, 2016;Hauk et al, 2018) revealing that when seniors, like any other segment of the population, are presented with technologies that are beneficial for their way of life, they tend to adopt them more readily (Kok et al, 2012), especially if such technologies will increase the level of their mental well-being (Cotten et al, 2013).…”
Section: Tqm 305supporting
confidence: 91%
See 2 more Smart Citations
“…At a broader level, our results are in accordance with the recent literature of technological acceptance (e.g. Caro et al, 2016;Hauk et al, 2018) revealing that when seniors, like any other segment of the population, are presented with technologies that are beneficial for their way of life, they tend to adopt them more readily (Kok et al, 2012), especially if such technologies will increase the level of their mental well-being (Cotten et al, 2013).…”
Section: Tqm 305supporting
confidence: 91%
“…Anabel et al (2016) focused their study on the activities that motivate digital seniors to engage in the use of the ICT in their daily life. The study revealed that when seniors, like any other segment of the population, are presented with technologies that are beneficial for their way of life, they tend to adopt them more readily (Kok et al, 2012), especially if such technologies will increase the level of their mental well-being (Cotten et al, 2013).…”
Section: Active Senior Travelers' Heterogeneity and Use Of Technologymentioning
confidence: 99%
See 1 more Smart Citation